Transforming Rural Governance through Enhanced Communication Strategies for Global Impact: Mengubah Tata Kelola Pemerintahan Pedesaan melalui Strategi Komunikasi yang Ditingkatkan untuk Dampak Global - Sindiana, Dina Ayu; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the implementation challenges of a Website-Based Village Information System in Dukuhsari Village Government, focusing on communication, resource allocation, disposition, and bureaucratic structure. Through qualitative methods including interviews and observation, the study reveals gaps in communication and resource management, impacting the system's effectiveness. The findings emphasize the need for improved communication strategies, consistent training, and ongoing support to optimize the system's utility and enhance public service delivery in Dukuhsari Village. Highlight: Challenges in Village Information System Implementation: Communication and resource allocation. Improving System Efficiency: Enhanced communication strategies and consistent training. Impact on Governance: Transparency and accessibility in rural service delivery. Keyword: Village Information System, Implementation Challenges, Communication, Resource Allocation, Public Service Delivery